2003
DOI: 10.1037/0033-2909.129.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: Meta-analyses of sensitivity and attachment interventions in early childhood.

Abstract: Is early preventive intervention effective in enhancing parental sensitivity and infant attachment security, and if so, what type of intervention is most successful? Seventy studies were traced, producing 88 intervention effects on sensitivity (n = 7,636) and/or attachment (n = 1,503). Randomized interventions appeared rather effective in changing insensitive parenting (d = 0.33) and infant attachment insecurity (d = 0.20). The most effective interventions used a moderate number of sessions and a clear-cut beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

84
1,351
10
45

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,605 publications
(1,490 citation statements)
references
References 103 publications
(135 reference statements)
84
1,351
10
45
Order By: Relevance
“…Previous research has consistently shown that children and adolescents with secure attachments have an advantage on measures of language, academic, and social and emotional functioning (Bakermans-Kranenburg, Van IJzendoorn, Juffer, 2003;Waters, Weinfield, & Hamilton, 2000). Research around the world during the past 50 years has provided strong support for the idea that caregiver sensitivity and emotional availability are key in determining children's attachment security (Chisholm, 1998;O'Connor, 2003b).…”
Section: Contextual Factorsmentioning
confidence: 99%
“…Previous research has consistently shown that children and adolescents with secure attachments have an advantage on measures of language, academic, and social and emotional functioning (Bakermans-Kranenburg, Van IJzendoorn, Juffer, 2003;Waters, Weinfield, & Hamilton, 2000). Research around the world during the past 50 years has provided strong support for the idea that caregiver sensitivity and emotional availability are key in determining children's attachment security (Chisholm, 1998;O'Connor, 2003b).…”
Section: Contextual Factorsmentioning
confidence: 99%
“…Since Ainsworth's seminal work on attachment security and maternal childrearing behaviors in her Uganda and Baltimore samples (Ainsworth, 1967;Ainsworth, Blehar, Waters, & Wall, 1978), parental sensitivity has been considered one of the most important determinants of individual differences in attachment security (Main, 1999). Observational and experimental studies of attachment have generally confirmed this idea, although the mean effect size for the association between parental sensitivity and attachment security is relatively modest (in De Wolff & Van IJzendoorn's, 1997, meta-analysis, the combined effect was r ϭ .24; see also Bakermans-Kranenburg, Van IJzendoorn, & Juffer, 2003).…”
mentioning
confidence: 97%
“…Parents may be open to suggestions for change during a period when they realize that raising a baby creates problems that they might not be able to solve without assistance and interactive routines have not yet become fixed. Moreover, they may be more open to intervention activities and suggestions in the second half of the first year than in the period immediately after birth when adapting to new demands (see for meta-analytic support, Bakermans-Kranenburg et al, 2003).…”
mentioning
confidence: 99%